AUSTRIAN SCHOOL: DIRECTIONS OF INTELLECTUAL PROPERTY ANALYSIS - A. V. Kovalev (Наука и техника)
Schools of economic thought being on the periphery of the up-to-date mainstream make a significant contribution to science developing methodology, improving own theories and formulating a problematic field of several actual problems which are to be solved by all the schools. One of the directions of  such contribution made by the Austrian school is an attitude of economic science to intellectual property right. Indisputable support of  a property right as such being disseminated on an intellectual property by some representatives of the school faces objections in respect of the given particular case from the side of its other representatives. The paper analyzes various school approaches to the intellectual property right.